Signal Integrity Engineering Redefined: To Include RF Stages Deploying CMOS VLSI Devices and Traces (As in Bluetooth) - Neelakanta, Perambur; Talbot, Bethany; De Groff, Dolores; Portal, Diana; Noori, Aziz (Transactions on Engineering and Computing Sciences, 2025)
This paper revisits the general definition of signal integrity (SI) engineering to include relevant considerations applied to RF stages (front- and/or back-end) of wireless system compliant devices such as Bluetooth, ZigBee, mobile phone etc. Apart from traditionally viewed (baseband) impairments specific to digital waveforms, possible artifacts caused by RF-stage electromagnetics that influence the SI undesirably are identified. Hence, SI is redefined more comprehensively to include RF contexts. Relevant ADSTM-based simulation results on transmit-receive (TR)-switch performance in a CMOS-VLSI based Bluetooth circuit are presented and discussed.